Determination of Importance Given to Control Forest Pest and Time Allocated to Them (A Case Study of Denizli Forest Enterprise Directorate) - İsmail Şafak; Emre Göksu (Doğal Afetler ve Çevre Dergisi)
In this study, the differences between in terms of the importance given to seasonal activities/works and the percentage of time allocated to them were investigated on the field of control of forest pests in Denizli Forest Enterprise Directorate. It was taken the seasonal views of all forest protection officers and forest engineers by the questionnaire forms. Thus, the importance attributed to the types of work and the percentage of allocated time for each type of work were obtained seasonally. Percentage of time spent in the questionnaires was evaluated at 100% for each question. In order to evaluate the level of importance given to each type of work, the nine-point Likert scale was used. When 14 forestry activities were evaluated generally, protection and forest crimes were determined as the most important subject with average 8.3 points. The activities under the International Cooperative Programme on Assessment and Monitoring of Air Pollution Effects on Forest (ICP) (5.0) were of minimum importance. When investigated in terms of allocated time, activities for determining the protection and forest crime were maximum spent of time (17.7%) and activities for quarantine measures and practices were minimum spent of time (3.5%).